2019
DOI: 10.1093/nutrit/nuz033
|View full text |Cite
|
Sign up to set email alerts
|

Is hypovitaminosis D associated with fibromyalgia? A systematic review

Abstract: Context Recent findings have suggested a high prevalence of vitamin D deficiency or insufficiency in fibromyalgia (FM) patients despite the lack of clinical and pathophysiological evidence. Objective A systematic review was conducted to examine the association between vitamin D status and FM, including the effect of vitamin D supplementation. Data source PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 106 publications
0
13
0
8
Order By: Relevance
“…In some systematic reviews, a correlation between vitamin D deficiency and fibromyalgia was determined, whereas its role in the pathophysiology and its clinical relevance requires further controlled studies [12,49]. More recent reviews reported as inconclusive the relationship between hypovitaminosis D and FMS, although vitamin D supplementation was considered as a co-adjuvant in FMS therapy [50]. Finally, although it is known that the absorption of B group vitamins like niacin and riboflavin is reduced by psychological factors, stress, and the use of sleeping-inducing drugs (which is common in FMS patients) [51], there are no studies in the literature about the efficacy of these supplementations in fibromyalgia patients.…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…In some systematic reviews, a correlation between vitamin D deficiency and fibromyalgia was determined, whereas its role in the pathophysiology and its clinical relevance requires further controlled studies [12,49]. More recent reviews reported as inconclusive the relationship between hypovitaminosis D and FMS, although vitamin D supplementation was considered as a co-adjuvant in FMS therapy [50]. Finally, although it is known that the absorption of B group vitamins like niacin and riboflavin is reduced by psychological factors, stress, and the use of sleeping-inducing drugs (which is common in FMS patients) [51], there are no studies in the literature about the efficacy of these supplementations in fibromyalgia patients.…”
Section: Nutrient Considerationsmentioning
confidence: 99%
“…1 FM patients are usually responded to the vitamin D supplementation which can consider as a co-adjuvant nutraceutical in FM therapy. 2 Vitamin D supplementation of 50000UI weekly for 8 weeks improved the scores of the questionnaires that related to the fibromyalgia, sleep, pain, but not the quality of life as assessed by short Form-36 in FM patients with low vitamin D levels of insufficient category. 3 Moreover, vitamin D supplementation of 50000 UI once weekly for 12 weeks non-significantly reduced the number of tender points in FM patients with insufficient category of serum vitamin D. 4 Interestingly, vitamin D supplementation improves non-significantly the score of widespread pain which is not Backgrounds and objective: Recent research focus of the association of low serum vitamin D level with the fibromyalgia.…”
Section: Introductionmentioning
confidence: 86%
“…The connection between vitamin D and FM has been widely studied [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121]. However, the relationship between vitamin D deficiency and FM is controversial among literature.…”
Section: Vitamin D In the Treatment Of Fibromyalgiamentioning
confidence: 99%